Root canal treatment and special needs patients. (5th July 2014) - Yap, E.; Parashos, P.; Borromeo, G. L.
Abstract Aim To identify current trends of root canal treatment for patients with special needs. Methodology A postal questionnaire was sent to General Dentists in Victoria, Australia and Endodontists and Special Needs Dentists across Australia to determine the extent of root canal treatment performed on special needs patients. Results Over a four‐month period, 1120 questionnaires were distributed with an overall response rate of 63.9% (n = 716). Response rates were 63.2% (n = 655), 68.5% (n = 50) and 100.0% (n = 11) amongst General Dentists, Endodontists and Special Needs Dentists, respectively. Endodontists (95.7%) and Special Needs Dentists (100.0%) performed significantly more root canal treatment on adult patients with special needs compared with 51.2% of General Dentists, (P < 0.001 and P = 0.001 respectively; Fisher's exact test). The most common reasons for not undertaking root canal treatment included limited cooperation, poor oral hygiene and uncontrolled movement. Amongst General Dentists, 75.7% opted for extraction in preference to root canal treatment. Significantly, more specialist practitioners performed root canal treatment utilizing conscious sedation (P < 0.001) and general anaesthesia (P = 0.003). Most specialist practitioners (69.1%) had undertaken single‐visit root canal treatment on special needs patients compared with only 29.7% of General Dentists (P < 0.001). Conclusions Root canal treatment in special needs patients was more likely to be carried out by specialist dental practitioners who were more likely to utilize a pharmacological approach for behaviour guidance and to perform single‐visit root canal treatment compared with General Dentists. A multidisciplinary approach for special needs patients who require root canal treatment provides an opportunity for these patients to retain their dentition.